Application of the Two Rowed Weyl Module in the Case of Partitions (7,7) and (7, 7) / (1, 0) - Khudair, Nubras Yasir; Hassan , Haytham Razooki (Iraqi Journal of Science, 2020)
The purpose of this paper is to study the application of Weyl module’s resolution in the case of two rows which will be specified in the partitions (7, 7) and (7, 7) / (1, 0), using the homological Weyl (i.e. the contracting homotopy and place polarization).